Harry McQueen folklore collection. - McQueen, Harry, 1910-1994 (1970)
Sound recordings relate to folk music.
Folkloric recording.
Recordings in the collection are not necessarily all performances, some are interviews.
Recorded from 1970 to 1992 at various locations.
Digital master available
Collection donated by Mrs Olive McQueen in 1994.
Harry McQueen was an accordion player with a broad dance music repertoire.
Summary not yet available.
Keywords: McQueen, Harry, -- 1910-1994.; McQueen, Harry, -- 1910-1994 -- Interviews; Folk musicians -- Australia; Accordion music; Folk dance music -- Australia; Folk music -- Australia; Country life -- Australia; Folk musicians